If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -14x = 7 + -9x Solving -14x = 7 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. -14x + 9x = 7 + -9x + 9x Combine like terms: -14x + 9x = -5x -5x = 7 + -9x + 9x Combine like terms: -9x + 9x = 0 -5x = 7 + 0 -5x = 7 Divide each side by '-5'. x = -1.4 Simplifying x = -1.4
| x^2-9x-3=-8x-1 | | 3x+4=58-3x | | x^2+4x-28=4 | | 3x+9=79-7x | | -14x=7-9 | | Damn=you | | 10x=90-5x | | 4(3w+5)-30=7w | | 4x+10=40-2x | | x^2+3x-13=2x-1 | | 6x=15+3x | | x^2-2x-4=4 | | 5x+6-1=18+4x-6 | | 64-2x=7x+23 | | 4x+28=13x-81 | | 3x+3x-3+7=3x+11 | | 4x+28=13x-18 | | 10x+26=5x+141 | | A+12+2=5+5+5 | | 12-10x=25-17x | | 2x+18=58-3x | | -45+7X=32 | | 3x+6=26-2x | | 8x=16+-4x | | 8x=16+-4 | | 10x=60-10x | | 4x-12x^2=0 | | t(t+2)(t-2)+2=0 | | t^3-4t+2=0 | | 2X-22=10 | | X+25=36 | | -7x=14+5x |